Features of the management of the territories of National nature parks - Shershun, M.; Mykytyn, T. (Land Management, Cadastre and Land Monitoring, 2023)
According to the data of the State Cadastre, at the beginning of 2021, the nature reserve fund counted 8,633 territories and objects with a total area of 4.1 million hectares, which was 6.8% of the country’s area. These territories are under the authority of various departments. The main purpose of protected areas is to preserve unique landscapes, species of flora and fauna for future generations. Today, the task is to increase the area of the nature reserve fund. It has been established that national natural parks (NPPs) are one of the largest objects of the protected fund in terms of area. To date, 56 NPPs have been created, which occupy an area of 1,399,161 hectares, which is 30.6% of the entire nature reserve fund. Administrations have been created in national parks to implement the functions entrusted to the park. These include preservation and protection of unique landscapes, conducting scientific research, recreational activities and educational work. The territory of the park includes lands of different purposes. These are mainly forests and other wooded areas (60%), the sea - 21%, inland waters - 6%, agricultural land - 5%, For the effective management of the national natural park, projects are being developed for the organization of the territory of the NPP for the protection, reproduction and recreational use of its natural complexes and objects. At the same time, a project approach is used, which makes it possible to achieve the strategic goals of the park with the help of the proposed measures. It is proposed to grow energy willow on agricultural lands. The environmental component of the project is important, as we have zero carbon emissions when using willow as fuel, which is important at the current price of energy resources. A technological map of growing has been developed, the efficiency of growing energy willow in the territories of the Nobel NPP has been calculated. Key words: nature reserve fund, national natural park, project of organization of the territory of the national natural park, energy willow.